T-cell antigen CD28 mediates adhesion with B cells by interacting with activation antigen B7/BB-1. - Linsley, P S (1990)
Studies using monoclonal antibodies (mAbs) have implicated the homodimeric glycoprotein CD28 as an important regulator of human T-cell activation, in part by posttranscriptional control of cytokine mRNA levels. Although the CD28 antigen has functional and structural characteristics of a receptor, a natural ligand for this molecule has not been identified. Here we show that the CD28 antigen, expressed in Chinese hamster ovary (CHO) cells, mediated specific intercellular adhesion with human lymphoblastoid and leukemic B-cell lines and with activated primary murine B cells. CD28-mediated adhesion was not dependent upon divalent cations. Several mAbs were identified that inhibited CD28-mediated adhesion, including mAb BB-1 against the B-cell activation antigen B7/BB-1 and some mAbs against major histocompatibility complex class I antigens. B7/BB-1 expression correlated closely with CD28-mediated adhesion, but class I expression did not. Transfected COS cells expressing the B7/BB-1 antigen adhered to CD28+ CHO cells; this adhesion was blocked by mAbs to CD28 and B7/BB-1. The specific recognition by CD28 of the B-cell activation antigen B7/BB-1 represents a heterophilic interaction between members of the immunoglobulin superfamily that may serve to regulate T-cell cytokine levels at sites of B-cell activation.